ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN WANITA SINGLE PARENT DI KECAMATAN BULELENG KABUPATEN BULELENG - Hartono, Farhan Rafid; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Women have a role can be highlighted in the development. The purpose this study 1) analyze effect of age, education, and the number of family dependents on the allocation of single parent women's work hours. 2) analyze effect of age, education, and number of family dependents on income of single parent women. 3)  analyze effect of age, education and the number of dependents of family indirectly income through the allocation of working hours for single parent women. This study uses primary and secondary data, sample 101 people and using path analysis techniques. Results of the study 1) Age had a negative significant effect on the allocation of working hours, while Education and family dependents had positive significant effect on the allocation of working. 2) Education, family dependents and allocation of working have positive significant effect on the income of single parent women, while age has a negative significant effect on the income of single parent women. 3) Age indirectly doesn’t affect the income of single parent women through allocation of working, while education and family dependents indirectly influence the income of single parent women through the allocation of working hours.   Keywords: age, education, number of family dependents, allocation of working hours and income of single parent women.